Becoming a social worker: Personal and professional identity formation among social welfare officers in Ghana (Journal of Comparative Social Work, 2023)
Despite being the subject of numerous research, professional identity in social work remains an important yet contentious concept. The aim of this article is to contribute to the literature on professional identity in social work by reflecting on the mutual development of the personal and professional identities of social workers in Ghana. Interviews were conducted among 20 social workers in two regions of Ghana, the northern and central regions. The evidence shows that the identity of social workers is shaped by two major factors – the statutory legal regime in which they operate, and the professional principles they apply in their work. Understood within the frame of social identity theory, the narratives of the social workers indicate how identifying with the professional group bestows distinctiveness and a change in personal identity. This change is reflected in their attitudes and value judgements of previously taken-for-granted socio-cultural practices. But while they firmly identify with the state and the professional principles, the social workers actively attempt to build local authenticity into their professional practices.